FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENGELOLAAN DAERAH TERHADAP TINGKAT KEMISKINAN DI KABUPATEN MAGELANG - hafan, fauziah aulia; Panggiarti, Endang Kartini (Fakultas Ekonomi Universitas IBA, 2020)
This article aims to analyze the performance of regional financial management and its influence on poverty levels in Magelang District in the period 2015-2018. The research methodology used is quantitative descriptive analysis and linear regression analysis related to the ratio of regional finances and the percentage of poverty using secondary data from BPPKAD Magelang Regency and BPS Magelang Regency. The results showed that the performance appraisal of Magelang Regency is 1) low independence ratio, 2) poor capability ratio, 3) the harmony of spending ratio is still not compatible, 4) effective financial effectiveness ratio, 5) inefficient financial efficiency ratio, 6) financial growth ratio low. And the performance of regional financial management in Magelang Regency by calculation using financial ratios has no significant effect on poverty levels in Magelang Regency.